Existence results in weighted Sobolev space for quasilinear degenerate p(z)−elliptic problems with a Hardy potential - Zineddaine, Ghizlane; Sabiry, Abdelaziz; Melliani, Said; Kassidi, Abderrazak (Mathematical Modelling and Analysis, 2024)
The objective of this work is to establish the existence of entropy solutions to degenerate nonlinear elliptic problems for L1-data f with a Hardy potential, in weighted Sobolev spaces with variable exponent, which are represented as follows where is a Leray-Lions operator from into its dual, is a non-linearity term that only meets the growth condition, and ρ > 0 is a constant.